Globalization and Income Inequality Revisited - Florian Dorn; Clemens Fuest; Niklas Potrafke (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2018)
This paper re-examines the link between globalization and income inequality. We use data for 140 countries over the period 1970–2014 and employ an IV approach to deal with the endogeneity of globalization measures. We find that the link between globalization and income inequality differs across different groups of countries. There is a robust positive relationship between globalization and inequality in the transition countries including China and most countries of Middle and Eastern Europe. In the sample of the most advanced economies, neither OLS nor 2SLS results show any significant positive relationship between globalization and inequality. We conclude that institutions providing income insurance and education, which characterize most advanced economies but are less developed in transition economies, may have moderated effects of globalization on income inequality.
Keywords: D31; D63; F02; F60; C26; H11; H20; 330; Globalization; income inequality; redistribution; instrumental variable estimation; panel econometrics; development levels; transition economies; China